EKSPERIMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) DAN TIPE ROUNDTABLE DISERTAI DENGAN ASSESSMENT FOR LEARNING (AFL) MELALUI PEER-ASSESSMENT PADA PRESTASI BELAJAR MATEMATIKA DITINJAU DARI ADVERSITY QUOTIENT (AQ) SISWA - Hr, Bq Malikah; Budiyono, Budiyono; Sari S, Dewi Retno (Jurnal Pembelajaran Matematika, 2015)
Abstract: The purposes of the research were to determine: (1) which learning models that produces better mathematics achievement, TSTS-AfL (TSTS type accompanied by AfL through peer-assessment), R-AfL (roundtable type accompanied by AfL through peer-assessment), or CL (classical learning); (2) which students that have better mathematics achievement, students with climbers type, campers, or quitters; (3) in each type of AQ, which of the tree learning models that produces better mathematics achievement; (4) in each learning model, which of the tree types students that have better mathematics achievement. The research was a quasi-experimental research, with a factorial design 3x3. The population was all students of State Senior High School in East Lombok of 2014/2015. The sample obtained was 347 students. Instruments in the research were mathematics learning achievement test and AQ questionnaire. The data was analyzed using two-way analysis of variance with unequal cells. The results of the research indicated as follows: (1) TSTS-AfL produces better mathematics achievement than R-AfL and CL, R-AfL produces better mathematics achievement than CL; (2) Students with climbers type have better mathematics achievement than campers and quitters, students with campers type have better mathematics achievement than quitters; (3) For the students with climbers and quitters type, the use of TSTS-AfL produces mathematics achievement as well as R-AfL and better than CL, R-AfL produces mathematics achievement as well as CL. For the students with campers type, the use of TSTS-AfL produces mathematics achievement as well as R-AfL and better than CL, R-AfL produces better mathematics achievement than CL; (4) Of TSTS-AfL, students with climbers type have mathematics achievement as well as with campers and better than quitters, campers type have achievement as well as quitters. Of R-AfL, students with climbers type have mathematics achievement as well as campers and better than quitters, and campers type have better mathematics achievement then quitters. Of CL, all of the type had the same mathematics achievement.Keywords: Cooperative learning model of TSTS type, Roundtable type, Peer-assessment, Adversity quotient and Mathematics achievement